PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR WILAYAH KEMENTRIAN AGAMA PROVINSI SULAWESI TENGGARA - Oktaviani, Dewi; Mokodompit, Eliyanti A.; Taufik, Muh.; Wati, Enny; Sabri, Sabri (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
The aim of this study; (1) To determine the effect of work ability on employee performance in the Regional Office of the Ministry of Religion of Southeast Sulawesi Province. (2) To determine the effect of work motivation on employee performance at the Regional Office of the Ministry of Religion of Southeast Sulawesi Province. (2) To determine the effect of work ability and work motivation simultaneously on employee performance at the Regional Office of the Ministry of Religion of Southeast Sulawesi Province. This type of research is quantitative with a sample of 61 people. The method of determining the sample is Incidental Sampling or determining the sample based on coincidence. The data analysis technique used was multiple linear regression analysis using the SPSS Version 22 application. The results showed that: (1) Work ability and work motivation have a positive and significant effect on employee performance. (2) work ability has a positive and significant effect on employee performance. (3) Work motivation has a positive and significant effect on employee performance.